Detection of SARS-CoV-2 in Ascitic Fluid of Cirrhotic COVID-19 Patients: Case Series and Literature Review - Grazia Caci; Andrea Marino; Edoardo Campanella; Ylenia Russotto; Cristina Micali; Natascia Laganà; Aldo Sitibondo; Roberto Filomia; Antonino Botindari; Serena Spampinato; Giuseppe Mancuso; Angelina Midiri; et al. (COVID)
SARS-CoV-2 has been identified in multiple organs and fluids, including the liver and peritoneal fluid. Gastrointestinal symptoms, such as abdominal pain, diarrhea, nausea, and vomiting, can exacerbate COVID-19 outcomes by contributing to complications, like acid–base imbalances and cardiovascular dysfunction, particularly in patients with pre-existing conditions. We report three cases of COVID-19 cirrhotic patients with SARS-CoV-2 detected in their ascitic fluid and review the relevant literature on the virus’s presence and clinical significance in peritoneal fluid. These findings underscore diagnostic and prognostic challenges in managing COVID-19 in patients with chronic liver disease and highlight the need for further research to clarify viral dissemination mechanisms and optimize protective measures for healthcare workers during surgical procedures.